Keynes, keynesianizem in razvojne spremembe sodobne države blaginje - renesansa ali zaton keynesianske teoretske paradigme - Kovač, Bogomir (Naše gospodarstvo, 2006)
The author took Keynes and Keynesianism as a model of modern economic science from the point of view of a particular research program. We cannot evaluate Keynes and plausible explanations of his work without the recent debate over the nature of scientific progress and the political economy of its ideologization. Politics and ideology and not macroeconomics are the main contributions of Keynes to contemporary economics. From that point of view, Keynesianism lives through the modern welfare state. Keynes is neither a contractarian liberal nor a liberal opponent of the state; therefore, his normative foundation may be the starting point of the transformation of a social welfare state to a liberal one.
Keywords: Keynes, John Maynard, 1883-1946; keynesianizem; ekonomske teorije; neoklasična ekonomska teorija; država blaginje; socialna država; welfare state